Nonunion Representation in Law and Practice - Taras, Daphne (Canadian Labour and Employment Law Journal, 2017)
This article provides a brief overview of the development of the Canadian approach to nonunion employee representation. For a century or more, nonunion representation vehicles have been used by workers and employers, without the attention, oversight and statutory regime that characterizes union-management relations. Nonunion representation rarely intersects with the law, and usually does so only when there is a collision between nonunion vehicles and trade unions during union organizing. Otherwise, the law is silent about nonunion representation. In the aftermath of the Supreme Court's contemporary analyses that commenced in 2001 with Dunmore, and moved through B.C. Health, Fraser, MPAO, and Meredith, the status of nonunion representation has not changed; these vehicles remain lawful. But there is considerable uncertainty about future directions. Might nonunion representation vehicles now be protected as collect- ives under the Charter, or will their somewhat sub-rosa nature remain? Should policy-makers and courts respect their maneuverability, or regulate them as inferior to unions? Certainly the Supreme Court has expressed distaste for these vehicles, as in the 2015 MPAO decision, but to what extent will this opprobrium find its way into Canadian law? We are at a crossroads, and if there is a legal challenge involving the status of nonunion collectives, there is no way of pre- dicting the outcome. In this article, the author discusses how an argument might be made that nonunion associations' activities could achieve Charter protection, and raises questions to which there are no clear answers.